Imprisoned mothers in Victorian England, 1853–1900: motherhood, identity and the convict prison: - Johnston, Helen (Criminology & criminal justice, 2019)
This article explores the experiences of imprisoned mothers in the Victorian convict prison system. It argues that motherhood, of central importance to the ideals of Victorian femininity, was disrupted and fractured by women’s long-term imprisonment. Using ‘whole life’ history methodology, the article draws on research into 288 women imprisoned and then released from the prison system, of whom half were mothers. It illuminates how the long-term prison system dealt with pregnancy, childbirth and family contact for female prisoners. It argues that while institutional or state care was often an inevitable consequence for children of single or widowed mothers, women used their limited resources and agency to assert their identity as mothers and direct outcomes for their children. But for others, prolific offending and multiple long sentences would render any chance of motherhood impossible.